2021
DOI: 10.1007/s43452-021-00192-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of innovative three-element binder on permanent deformations in recycled mixtures with emulsion and foamed bitumen

Abstract: This article is detected to the assessment of durable deformations of recycled mixtures made of foamed bitumen (MCAS) and emulsion (MCE). In the basic part of research and analyses, attention was focused on determining the scale of three-component composition modifying rheological phenomena of recycled mixtures and other selected features considering various methods of bituminous binder proportioning. Cement, hydrated lime, and dusts from cement dust extracting system were included in the composition hydraulic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The properties of mixtures containing RAP with virgin aggregate and cement-emulsion mortar are known for practical use as mineral-cement-emulsion mixtures (MCEM). In Poland, first requirements were published in 1999 by IBDiM Issue 61 [ 3 ], since then many years of laboratory and field research [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] also FWD measurements of pavement after 13 years of using [ 12 ] have been made. The disadvantages of MCEM base courses in Poland include mainly: transverse cracks, accelerated degradation in the weakest places of the layer where fatigue damage has reached the value of D = 50%, the commonly used “in situ” method that does not ensure uniformity of the layer made [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of mixtures containing RAP with virgin aggregate and cement-emulsion mortar are known for practical use as mineral-cement-emulsion mixtures (MCEM). In Poland, first requirements were published in 1999 by IBDiM Issue 61 [ 3 ], since then many years of laboratory and field research [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] also FWD measurements of pavement after 13 years of using [ 12 ] have been made. The disadvantages of MCEM base courses in Poland include mainly: transverse cracks, accelerated degradation in the weakest places of the layer where fatigue damage has reached the value of D = 50%, the commonly used “in situ” method that does not ensure uniformity of the layer made [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most developed bitumen emulsions are used for road construction [5][6]. They provide adhesion of pavement layers, used in surface treatment and for soil reinforcement and stabilization [7]. They are cation-active [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that an adequately designed binder will significantly modify the viscoelastic properties, thus helping to avoid deformations due to long-term loading. In [14], Mazurek et al reported the results of a comprehensive creep analysis for the CRM-FB containing a binder mix composed of cement, hydrated lime and dust derived from de-dusting systems. They demonstrated that changes in the ratios of mixed binder components significantly modify the deformation rate in the recycled layer and the maximum depth of permanent deformation and that numerical methods can be used to predict these changes.…”
Section: Introductionmentioning
confidence: 99%